West Indian Powderpost Drywood Termite, Cryptotermes brevis (Walker) (Insecta: Isoptera: Kalotermitidae) - Rudolf H. Scheffrahn; Nan-Yao Su (EDIS, 2002)
This document is EENY-079, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 1999.